Monitoring disease progression in childhood bronchiectasis - Kathryn A. Ramsey; André Schultz; André Schultz (Frontiers Media S.A., 2022)
Bronchiectasis (not related to cystic fibrosis) is a chronic lung disease caused by a range of etiologies but characterized by abnormal airway dilatation, recurrent respiratory symptoms, impaired quality of life and reduced life expectancy. Patients typically experience episodes of chronic wet cough and recurrent pulmonary exacerbations requiring hospitalization. Early diagnosis and management of childhood bronchiectasis are essential to prevent respiratory decline, optimize quality of life, minimize pulmonary exacerbations, and potentially reverse bronchial disease. Disease monitoring potentially allows for (1) the early detection of acute exacerbations, facilitating timely intervention, (2) tracking the rate of disease progression for prognostic purposes, and (3) quantifying the response to therapies. This narrative review article will discuss methods for monitoring disease progression in children with bronchiectasis, including lung imaging, respiratory function, patient-reported outcomes, respiratory exacerbations, sputum biomarkers, and nutritional outcomes.